Impact of Demographic Variables on Quality of Work Life: A Case Study ofMult! Speciality Hospitals of Chandigarh Tri city. - Dogra, Pooja (Gyan Management Journal, 2018)
The present study was conducted to find out the effect of demographic variables on quality of work life for the employees of selected public and private multi speciality hospitals of Chandigarh, Panchkula and Maha.Ii. Two public and two private hospitals were selected and total o/300 responses were taken I 150 from each category of hospitals. Managing a hospital has become more complex’with the advancement of technology and requirement of people from diverse backgrounds, as world is moving at high speed and there is intense competition, consumers are more aware the employees need to be . . customer oriented and hence there is requirement of quality of work life in hospitals too, so that the patients may get better quality of services. The study revealed that opinion of respondents was positive towards the quality of work life in multi speciality hospitals of Chandigarh tri city, the age had a significant impact on the QWL,_ thework experience also had significant impact on QWL, whereas gender and educational qualification were not significant.